Changing work and employment relations in German industries: Breaking away from the German model? - Ulrich Jürgens; Martin Krzywdzinski; Christina Teipen (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2006)
In this paper, we examine employment relationships as an important dimension of the ,,German model“. There is a long tradition of debate regarding a specific “German model” comprised of institutions and practices in this area, including the partnership of labour and capital symbolised by the system of co-determination; patterns of long-term employment for many employees, an emphasis on skills and correspondingly high investments in vocational training, competition based on quality production, often targeting upper market segments. Is this model changing? Do we even witness a break of this model? We analyse processes at the micro and meso level. We suppose that the reorganisation of industry structure and of value chains, and the transformation of business models of enterprises are important drivers of changing employment relationships. We have chosen three industries for our analysis that allow a “most different cases” comparison: The automotive industry, the telecommunications equipment industry, and the video games industry. First, the automotive industry is a successful and highly competitive case of industrial development in Germany and represents best the “classical” German model of employment relationships. The telecom equipment industry and the video games industry are parts of the large complex of so called infocom industries representative of the “New Economy”. It is often claimed that the development of these industries is not compatible with the framework for employment relations characterizing countries like Germany. Is this assertion true? We find similar trends but differences in patterns and pace of change in the automobile and in the telecommunications equipment industries. In both industries, the binding force of industry-wide agreements declines. In both industries, the employees have to accept wage reductions and increasing flexibility to maintain their employment security. In both industries, the outsourcing and offshoring pressures are very strong and entail deep changes in the balance of power between actors. The video games industry stands apart because the institutions of the German model have very limited applicability to this industry. But do the changes represent a break with the “German model”? It seems that in the current situation, two scenarios of development are still possible: A gradual adaptation to new conditions and a radical break from the hitherto trajectory.
Keywords: 300; Arbeitsbeziehungen; Arbeitsmarktflexibilisierung; Kraftfahrzeugindustrie; Telekommunikation; Softwareindustrie